Kualitas Lingkungan Keluarga di Kawasan Candi Batujaya - Elmanora Elmanora; Mulyati Mulyati; Kenty Martiastuti (Universitas Al Azhar Indonesia, 2023)
The quality of the family environment is one of the important foundations in building a good society. This study aims to analyze the quality of the family environment that lives in the Batujaya Temple area, Karawang Regency, West Java Province, Indonesia. Data has been collected from April to May 2019. This study was involved 100 families that have been selected using simple random techniques. Data consist of family characteristics and the quality of the family environment. The quality of the family environment was measured using the